Fiduciary duty in the relationship of aboriginal peoples and the Canadian military. - Weatherston, Alex. (University of Ottawa (Canada), 1993)
This thesis is a legal analysis of the fiduciary duty in the relationship between the Crown and Aboriginal Peoples in Canada as it specifically applies to the exercise of power by the Federal Government for national defence under section 91(7) of the Constitution Act, 1867, the federal power of "Militia, Military and Naval Service, and Defence," and under the royal prerogative. Aboriginal and treaty rights may be infringed by defence activities conducted by the Canadian Forces and by foreign military allies training in Canada. Defence activities usually occur in non-residential areas in Canada and it is these areas that Aboriginal and treaty rights are often exercised by the holders of these rights. In applying the justification test developed in Sparrow to the infringement by defence activities of Aboriginal and treaty rights that are now "recognized and affirmed" in subsection 35(1), I submit in the thesis that different legal interests need to be considered in assessing the justification of such activities. An assessment of justification would be made to ensure that the honour of the Crown was upheld and that any necessary infringement was minimized in resolving the conflict of interest. This assessment would be based on a full examination of the conduct of the Crown and of defence officials in the planning and implementation of any defence activity with real or potential impact on section 35 rights. Such an examination would involve considerations such as planning and identification of Aboriginal and treaty rights potentially affected in defence areas; alternative defence activities considered; consultation with Aboriginal Peoples; disclosure of information to Aboriginal Peoples concerning planned defence activities; the record of consideration by defence officials of information provided by affected Aboriginal Peoples; the adequacy of compensation for affected or extinguished rights; completion of other statutory reviews; and proportionality of degree or seriousness of infringement and effort to minimize. (Abstract shortened by UMI.)
Keywords: Law.